Microbiology, resistance patterns, and risk factors of mortality in ventilator-associated bacterial pneumonia in a Northern Thai tertiary-care university based general surgical intensive care unit - Chittawatanarat,K. (Dove Medical Press Ltd., 2015)
Background: Ventilator-associated pneumonia (VAP) occurrence, causative pathogens, and resistance patterns in surgical intensive care units (SICU) are different between Western and developing Asian countries. In Thailand, resistant organisms have progressively increased in the last decade. However, the evidence describing causes of VAP and its outcomes, especially secondary to resistant pathogens, in Asian developing countries' SICUs is very limited. Therefore, the objective of this study was to describe the incidence, pathogen characteristics, and risk factors that impact mortality and patient survival following VAP in a tertiary Northern Thai SICU. Methods: Between 2008 and 2012, VAP occurred in a total of 150 patients in Chiang Mai University's general SICUs (6.3±2.8 cases per 1,000 mechanical ventilator days). The following clinical data were collected from 46 patients who died and 104 patients who survived: microbiologic results, susceptible patterns, and survival status at hospital discharge. Antimicrobial susceptibility patterns were classified as susceptible, multidrug resistant (MDR), extensively drug resistant (XDR), and pan-drug resistant (PDR). The hazard ratio (HR) was calculated for risk factor analysis. Results: Regarding the microbiology, gram negative organisms were the major pathogens (n=142, 94.7%). The first three most common organisms were Acinetobacter baumannii (38.7% of all organisms, mortality 41.4%), Klebsiella pneumoniae (17.3%, mortality 30.8%), and Pseudomonas aeruginosa (16.7%, mortality 16%) respectively. The most common gram positive organism was Staphylococcus aureus (4.0%, mortality 50%). The median day of VAP occurrence were significantly different between the three groups (P<0.01): susceptible (day 4), MDR (day 5), and XDR (day 6.5). Only half of all VAP cases were caused by susceptible organisms. Antibiotic resistance was demonstrated by 49.3% of the gram negative organisms and 62.5% of the gram positive organisms. Extensive drug resistance was evident only in Acinetobacter baumannii (30.6%) and Pseudomonas aeruginosa (1.3%). No pan-drug resistance was found during surveillance. The significant HR risk factors were age (P=0.03), resistant organisms (P=0.04), XDR (P=0.02), and acute physiology and chronic health evaluation II score (<0.01). Acinetobacter baumannii (P=0.06) and intubation due to severe sepsis (P=0.08) demonstrated a trend toward a significant increase in the HR. On the other hand, there were significantly decreased HRs in trauma patients (P=0.01). Initial administration of appropriate antibiotic therapy had a tendency toward a significant decrease in the HR (P=0.08). Conclusion: Gram negative organisms were the primary cause of bacterial VAP in Chiang Mai University's general SICU. Resistant strains were present in half of all VAP cases and were associated with the day of VAP onset. Regarding risk factors, age, acute physiology, chronic health evaluation II score, resistant organisms (especially XDR), and being a non-trauma patient increased the risk of mortality. © 2014 Chittawatanarat et al.